Role of HMGB1 in Cisplatin-Persistent Lung Adenocarcinoma Cell Lines - Chavez-Dominguez, Rodolfo L.; Perez-Medina, Mario A.; Lopez-Gonzalez, Jose S.; Galicia-Velasco, Miriam; Matias-Florentino, Margarita; Avila-Rios, Santiago; Rumbo-Nava, Uriel; Salgado-Aguayo, Alfonso; Gonzalez-Gonzalez, Claudia; Aguilar-Cazares, Dolores (Frontiers in Oncology, 2021)
Significant advances have been made recently in the development of targeted therapy for lung adenocarcinoma. However, platinum-based chemotherapy remains as the cornerstone in the treatment of this neoplasm. This is the treatment option for adenocarcinomas without EGFR gain-of-function mutations or tumors that have developed resistance to targeted therapy. The High-Mobility Group Box 1 (HMGB1) is a multifunctional protein involved in intrinsic resistance to cisplatin. HMGB1 is released when cytotoxic agents, such as cisplatin, induce cell death. In the extracellular milieu, HMGB1 acts as adjuvant to induce an antitumor immune response. However, the opposite effect favoring tumor progression has also been reported. In this study, the effect of cisplatin in lung adenocarcinoma cell lines harboring clinically relevant mutations, such as EGFR mutations, were studied. Subcellular localization of HMGB1 was detected in the cell lines and in viable cells after a single exposure to cisplatin, which are designated cisplatin-persistent cells. The mRNA expression of the receptor for advanced glycation end products (RAGE), TLR-2, and TLR-4 receptors was measured in parental cell lines and their persistent variants. Finally, changes in plasma HMGB1 from a cohort of lung adenocarcinoma patients without EGFR mutation and treated with cisplatin-based therapy were analyzed. Cisplatin-susceptible lung adenocarcinoma cell lines died by apoptosis or necrosis and released HMGB1. In persistent-cisplatin cells, nuclear relocalization of HMGB1 and overexpression of HMGB1 and RAGE, but not TLR-2 or TLR-4, were observed. In tumor cells, this HMGB1-RAGE interaction may be associated with the development of cisplatin resistance. The results indicate a direct relationship between plasma levels of HMGB1 and overall survival. In conclusion, HMGB1 may be an effective biomarker associated with increased overall survival of lung adenocarcinoma patients.